2013
DOI: 10.1194/jlr.m034157
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow NR4A expression is not a dominant factor in the development of atherosclerosis or macrophage polarization in mice

Abstract: The formation of the atherosclerotic lesion is a complex process influenced by an array of inflammatory and lipid metabolism pathways. We previously demonstrated that NR4A nuclear receptors are highly induced in macrophages in response to inflammatory stimuli and modulate the expression of genes linked to inflammation in vitro. Here we used mouse genetic models to assess the impact of NR4A expression on atherosclerosis development and macrophage polarization. Transplantation of wild-type, Nur77−/−, or Nor1−/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
2
45
4
1
Order By: Relevance
“…Again, no differences were found between WT and Nur77 Ϫ/Ϫ macrophages in TNF-␣, KC, and IL-6 production or in mRNA expression of several cytokines and chemokines known to be upregulated in this model. These results are not in agreement with data reported previously by our group and others, in which macrophages were stimulated with LPS (10,(16)(17)(18). One explanation may be that LPS is only one of a whole range of antigens present on E. coli bacteria.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Again, no differences were found between WT and Nur77 Ϫ/Ϫ macrophages in TNF-␣, KC, and IL-6 production or in mRNA expression of several cytokines and chemokines known to be upregulated in this model. These results are not in agreement with data reported previously by our group and others, in which macrophages were stimulated with LPS (10,(16)(17)(18). One explanation may be that LPS is only one of a whole range of antigens present on E. coli bacteria.…”
Section: Discussioncontrasting
confidence: 57%
“…In atherosclerosis bone marrow, specific deletion of Nur77 aggravates the disease, with vascular lesions containing more macrophages, T cells, and chemokine SDF-1␣ (16,17). Of note, it was also recently described that Nur77 does not affect atherosclerosis (18). Hanna et al (19) demonstrated that Nur77 Ϫ/Ϫ mice lack the patrolling Ly6C lo monocyte population in bone marrow, spleen, and blood.…”
mentioning
confidence: 99%
“…Macrophages from Nur77À/À mice show modifications in the expression of M2-specific markers with a shift toward a pro-inflammatory phenotype, exhibiting increased expression of M1-markers such as interleukin-12, interferon-g and nitric oxide synthase [23,24]. However, these results have been challenged by another study showing that NOR1 and Nur77 are not dominant actors in M2 macrophage polarization in the mouse [25].…”
Section: Introductionmentioning
confidence: 80%
“…Mice bearing the NOR1 mutant allele were mated as heterozygotes due to decreased fertility of the NOR1 Ϫ/Ϫ mice. Finally, we bred the MCK-Cre mouse (on a mixed C57BL/6J and C57BL/6N background) (catalog number 006475; The Jackson Laboratory) to the compound mutant to generate control ( Ϫ/Ϫ were reported elsewhere (25). Mice were fed ad libitum and maintained on a 12-h light-dark cycle and were age and gender matched for all experiments.…”
Section: Microarraysmentioning
confidence: 99%